Optimising taxonomic effort to overcome the Linnean shortfall: the case of European leaf beetles. Issue 5 (15th May 2017) - Freijeiro, Andrea; Gómez‐Rodríguez, Carola; Castro‐Insua, Adrián; Baselga, Andrés
Abstract: Assessing the factors that govern the probability of a species (i) being discovered and (ii) being described under different names can help to improve the efficiency of future taxonomic efforts. Here, we assess whether species body size, extent of distribution and geographical position affect the probabilities of discovery and redundant description of European Chrysomelidae (Coleoptera). The probability of description of European Chrysomelidae is determined mostly by the characteristics of the species distribution but not by body size; species with broad and northern distributions have been described before. The probability of redundant description is mainly related to the year of description; species with a higher number of synonyms were described earlier and have broader distributions. The extrapolation of the observed trends suggests that undescribed species of Chrysomelidae have narrow distributions and live in southern Europe and that recently described species have a low number of synonyms because the efficiency of leaf beetle taxonomy has increased over time.